FEATURES OF USING NONSTEROIDAL ANTI-INFLAMMATORY DRUGS IN DENTAL PRACTICE - A. K. Iordanishvili; A. I. Dyagilev; O. N. Risovannaya; V. Yu. Skorikov; V. L. Popkov (Кубанский научный медицинский вестник, 2018)
Aim. This study was conducted to assess the awareness of dentists about the questions of pharmacokinetics and pharmacodynamics of nonsteroidal anti-inflammatory drugs as well as to study the features of their use for the relief of pain syndrome in dental practice.Materials and methods. By means of the questionnaires were studied 107 dentists working in dental clinics and dental departments of General hospitals, especially their use of the nonsteroidal anti-inflammatory drugs for pain relief.Results. It was determined that 85% of doctors use non-selective and moderately selective cyclooxygenase inhibitors (COX), 15%-prefer Cox-2 inhibitor with the pronounced selectivity for pain relief. The highest number of correct answers was given by a group of doctors with work experience from 5 to 10 years (40.3%), the lowest – by doctors with work experience more than 20 years, respectively 40.3% and 36.1% of the total number of doctors from the studied groups.Conclusion. There was noted that it is necessary to pay attention to the peculiarities of pain relief for the improvement of dentists’ work as well as to involve clinical pharmacologists for these purposes.